The Validation of Neogen Reveal® Q+ for DON: AOAC Performance Tested MethodSM 071901. (29th January 2020) - Gray, R Lucas; Kostin, Alex; Anderson, Gabrielle; Roman, Brooke; Klein, Frank; Donofrio, Robert; Goto, Tetsuhito; Trucksess, Mary; Ziemer, Wayne
Abstract: Background: Reveal® Q+ for DON is an immunochromatographic test for quantitative determination of deoxynivalenol (DON) in grains. Objective: A study was conducted to validate performance of this method for determination of DON in naturally contaminated corn and wheat and in DON-spiked corn/soy blend, soybeans, barley, malted barley, buckwheat, brown rice, sorghum, and distillers dried grain. Methods: In addition to matrix testing, LOD, linearity, selectivity, robustness, and stability/lot-to-lot consistency testing were performed. Results: The LOD was determined to be 0.014 ppm in corn and 0.037 ppm in wheat, and the LOQ 0.042 ppm in corn and 0.11 ppm in wheat. Recovery ranged from 90 to 104% across a range of reference values of 0.5 to 34.5 ppm. Linearity calculation comparing test results with reference values produced R 2 values of 0.999 in both matrixes. Internal results with corn and wheat were corroborated in independent laboratory testing. For DON-spiked commodities, mean recovery across a range of DON concentration from 0.5 to 30 ppm ranged from 90 to 109%. Results of selectivity testing showed no cross-reactivity with other mycotoxins and no interference in detection of DON. Reagent lot-to-lot consistency and stability studies showed consistent results across a range of DON levels and established expiration dating for the test of 18 months after manufacture when stored under specified conditions. Conclusions and Highlights: The Reveal Q+ for DON test offers reliable performance as well as the advantages of aqueous sample extraction, procedural simplicity, minimal labor and equipment requirements, and rapid results. Conclusions: The Reveal Q+ for DON test is validated as a Performace Tested Method in Corn, Wheat, and a variety of other grains. Highlights: The test provides rapid results from a simple aqueous extraction and requires minimal labor and equipment.